Pengaruh Variasi Ukuran Partikel Bahan Biopelet Terhadap Laju Pembakaran Dan Kerapatan Massa Pada Limbah Kayu Mahoni - Wahidin Nuriana (JURNAL AGRI-TEK : Jurnal Penelitian Ilmu-Ilmu Eksakta, 2022)
The potential of biomass as an alternative energy source is very abundant, but not yet well managed. The purpose of this study was to determine the effect of 40 mesh, 60 mesh, 80 mesh, 100 size variations on biopelet waste on mass density values ??and combustion ratesThe potential of biomass as an alternative energy source is very abundant, but not yet well managed. Biomass is an organic material derived from leaves, twigs, dry grasses, agricultural waste and forestry waste. The purpose of this study was to determine the effect of 40 mesh, 60 mesh, 80 mesh, 100 size variations on biopelet waste on mass density values ??and combustion rates. Mahogany sawdust waste is sorted, then dried in the sun for 7 hours to reduce water content. Furthermore, mahogany wood powder is refined so that the size of the material becomes smaller. Then do the sifting with a variation of 40 mesh sieve, 60 mesh, 80 mesh, 100 mesh. Mahogany wood waste is sorted, then dried in the sun for 7 hours to reduce water content. Furthermore, mahogany wood powder is refined so that the size of the material becomes smaller. Then sieving with 40 mesh sieve variations, 60 mesh, 80 mesh, 100 mesh. Mahogany wood powder is mixed with adhesive using a ratio of 80% mahogany powder and 20% tapioca adhesive. Subsequently printed using a pressure of 115 kg / cm2, allowed to stand for 2 minutes removed from the mold. The results showed the effect of biopelet size on the characteristics of biopelet with the highest density at 100 mesh sieve size with a value of 1.151 g / cm3, and the lowest burning rate was obtained on biopelet with a size of 100 mesh material with a value of 3.58 g / min